Analysis Of The Causes Of Overlapping Land Certificates And Their Solutions (Case Study Of SHGB No. 114/Karangkempel And SHGB No. 115/Karangkempel) - Ivanda Adhis Permata Putri Ivanda (Faculty of Law, Universitas Negeri Semarang, 2025)
This study aims to analyze the causes of overlapping land certificates and solutions to resolve them for SHGB No. 114/Karangkempel and SHGB No. 115/Karangkempel with SHGB No. 1256/Bendan Ngisor. The problems studied are the causal factors that influence the overlapping of building use rights certificates so that the rights holders do not get legal certainty. The research method used is empirical juridical using a qualitative approach, which is sourced from literature and field data through observation, interviews and documentation. The results of the study indicate that there are several factors that cause the overlapping of building use rights certificates, including an administration system that is not yet strong, no maintenance of land boundaries by rights holders, and no digitalization. The conclusion of this study is that the BPN of Semarang City has a significant role in providing solutions to the overlapping cases. Several solutions such as mediation, strengthening administration, and socialization can be applied as a form of prevention and resolution of overlapping land disputes in Semarang City.